Upaya memenuhi kestabilan gula darah pada pasien diabetes melitus di rsud dr. Soehadi prijonegoro - KHASANAH, USWATUN; , Okti Sri Purwanti, S.Kep.,Ns.,M.Kep.,Ns.Sp.Kep.,MB (2016)
Introduction:Diabetes mellitus is a chronic disease characterized by the increasing of blood glucose. The case of diabetes mellitus increases due to genetic factors, obesity and unhealthy lifestyle. Since the blood glucose is not stable, it will cause various complications. Objective: The objective of this research was to provide an overview of an attemp to comply the stability of blood glucose in the patients with diabetes mellitus at dr. Soehadi Prijonegoro Hospital. Methods: The method applied was descriptive research with case study approach done toward the patients with diabetes mellitus in the Melati inpatient room of dr. Soehadi Prijonegoro Hospital on March 30th to April 1st, 2016. The process of data collection including observation, interview, physical examination, medical records, and journals review related to diabetes. Result: An attempt undertaken to comply the stability of blood glucose are through education, diet pattens, exercise, and medication. Conclusion: Most problems dealing with blood glucose can be done. Recommended management for diabetic patients is to obey the pattern that has been set, so that the program of blood glucose stability control can be achieved.